2012
DOI: 10.1007/s00249-011-0783-3
|View full text |Cite
|
Sign up to set email alerts
|

General analysis of competitive binding in drug–interceptor–DNA systems

Abstract: A general model of competitive binding in drug-interceptor-DNA systems has been developed in order to quantify both the interceptor and protector mechanisms. The model involves full parameterization of the basic equations governing the mutual competition between drugs binding to DNA and incorporates as partial cases various similar models existing in the literature. The generality of the model results from strict accounting of the statistical effects of the binding of the drug and interceptor with DNA accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…These features enable us to draw a parallel with the well-investigated drug-xanthine systems (Buchelnikov et al 2012;Evstigneev et al 2006Evstigneev et al , 2008Evstigneev et al , 2011Evstign eev 2010Evstign eev , 2013Goluriski et al 2013;Larsen et al 1996;Piosik et al 2010;Traganos et al 1991;Woziwodzka et al 2011), for which similar effects are observed on joint in vitro action of aromatic BACs. Of particular importance here is that in the drug-xanthine systems, the operation of the interceptor mechanism (i.e., the drugxanthine hetero-association) can be considered as widely accepted.…”
Section: Drug Action In the Presence Of C6fl Fullerenementioning
confidence: 93%
See 2 more Smart Citations
“…These features enable us to draw a parallel with the well-investigated drug-xanthine systems (Buchelnikov et al 2012;Evstigneev et al 2006Evstigneev et al , 2008Evstigneev et al , 2011Evstign eev 2010Evstign eev , 2013Goluriski et al 2013;Larsen et al 1996;Piosik et al 2010;Traganos et al 1991;Woziwodzka et al 2011), for which similar effects are observed on joint in vitro action of aromatic BACs. Of particular importance here is that in the drug-xanthine systems, the operation of the interceptor mechanism (i.e., the drugxanthine hetero-association) can be considered as widely accepted.…”
Section: Drug Action In the Presence Of C6fl Fullerenementioning
confidence: 93%
“…However, the study of such a mechanism is complicated by possible influence from other molecular processes, one of which is most often referred to as a 'protector' mechanism, i.e., the drug/interceptor competition for the binding sites on DNA (Buchelnikov et al 2012;Evstigneev 2010Evstigneev , 2013Evstigneev et al 2011;Goluriski et al 2013). Investigation of the interceptor and protector mechanisms for DNA-bind ing drugs used in combination is the subject of the theory of interceptor/protector action (Buchelnikov et al 2012;Evstigneev et al 2008Evstigneev et al , 2011Evstigneev 2010). Unfortu nately, the applicability of the protector mechanism within the system containing C6fl fullerene cannot be estimated on the basis of the currently available literature data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,36]). Partial derivative of N corr with respect to the monomer concentration C i at C i ¼ 0 extracts from N corr all terms related to complexes containing i-type monomer, whereas the value of N corr at C i ¼ 0 gives the part of N corr not containing the i-type monomer.…”
Section: Reduction Of Derived Equations To Partial Cases Known From Tmentioning
confidence: 99%
“…(32) at N ¼ 2 and N ¼ 3 enables one to get N ð1Þ corr identical to those derived in Refs. [35,36]. Detailed derivation of the grand partition function for above-mentioned case is outlined in Appendix D.…”
Section: Reduction Of Derived Equations To Partial Cases Known From Tmentioning
confidence: 99%